(untitled) (Research, Society and Development, 2021)
Food craving occurs for those foods that are more palatable, highly processed, with high levels of carbohydrates and refined sugars and/or fat. The direct relationship between changes in the ideal nutritional status (such as obesity) and cardiovascular, neurodegenerative, metabolic and inflammatory diseases and the increase in oxidative stress is already consolidated, however, for the analysis of sleep quality, there is still little evidence. To outline the profile of nutritional status, food craving, biochemical markers of inflammation and sleep quality in health professionals from a university hospital. This pilot study was cross-sectional, quantitative and prospective. The recruited participants were linked to a Brazilian University Hospital. The target population consisted of health professionals from the hospital’s clinical staff, who had been admitted for at least six months prior to the beginning of the research. Questionnaires were applied to measure Intense Food Cravings – Trait and State questionnaires; inflammation, recorded together with sociodemographic and body composition data from bioimpedance. For sleep assessment, the Pittsburgh Sleep Quality Index and the Epworth Sleepiness Scale were used. Statistically significant correlations were found between inflammation, sleep quality, phase angle and body fat percentage. It is inferred that moderate food cravings influence the quality of poor sleep, biochemical profile of inflammation and body composition of health professionals. We suggest further studies of longitudinal interventions that can assess these long-term relationships.